Molecular Imaging of Gastric Neoplasia with Near-Infrared Fluorescent Activatable Probes - Shengli Ding; Randall Eric Blue; Yijing Chen; Brooks Scull; Pauline Kay Lund; Douglas Morgan (Molecular Imaging)
Gastric cancer is the second leading cause of cancer mortality worldwide and is projected to rise to tenth in all-cause mortality in the near term. Early detection requires improved sensitivity and specificity of endoscopic imaging with novel methods. The objective of this study was to evaluate the utility of activatable molecular probes for the detection of gastric cancer both in vivo and ex vivo in a preclinical model. Smad4 +/− mice, which develop spontaneous gastric neoplasia, were compared to normal wild-type controls. Cathepsin-activatable and matrix metalloproteinase (MMP)-activatable molecular probes were injected 24 hours and 6 hours before imaging, respectively. In vivo imaging was performed using quantitative tomographic near-infrared fluorescence (NIRF) imaging. For validation, ex vivo imaging and histologic examination were performed. Molecular imaging in vivo of Smad4 +/− gastric cancer murine models revealed intense activation of both cathepsin B and MMP probes. Ex vivo imaging and histology confirmed that the detected neoplasms were adenocarcinomas and hyperplastic lesions. This study provides proof of principle that the cathepsin- and MMP-activatable molecular probes are activated in the Smad4 +/− murine model of spontaneous gastric adenocarcinoma and can be imaged by both in vivo and ex vivo NIRF methods. The cathepsin probe also detects hyperplastic lesions.